A 'certain hand' and its margin of error. Issue 1 (1st April 2021) - Boukla, Eirini
Suppose we consider an independent artist tolerance allows for a 'margin of error' as an aesthetic measure, it follows that its innate implication must impact on any, and all artworks, its intervention and the effects of its making. Seeing this independent tolerance, strangely, intersecting with a certain drawing and its erring in doing, this writing considers the link between error and an enduring measure of the artist's hand and reconsiders its indexical relation to the artist. The inquiry begins with a reflection on Katharina Hinsberg's (1999) Nulla dies sine linea ('No Day without a Line'), where error and a detached automated approach to drawing is emphasized. Going on, brings into the discussion Warhol's 'blotted line', which prefigures a notion of a 'failure of reproduction' and the production of its effects. Elaborating, on Hinsberg's subjective resistance and Warhol's failure of reproduction, the discussion brings on board Christopher Wool's, and Wade Guyton's technical execution and erring. Marked by craft, tools and by decisions about tools, Wool's and Guyton's work resolutely embraces the hand encumbering the reasoning of the mind's judgements and the use and fidelity of machined methods of reproduction. Wool's roller, stamp, stencil, and Guyton's skewed digital technologies, their operational error and technical failure take the mind and the hand back together, and demonstrate that perhaps the trace of the artist's hand, no matter how dispassionate, ironic or vacuous of meaning stubbornly remains a drawing's most compelling message.